Relevance of using the equipment for control of fishing gear to reduce inaccuracy in evaluation of marine organisms abundance - Egor A. Zakharov; Pavel O. Emelin (Известия ТИНРО, 2016)
Geometric parameters of the bottom trawl DT 27.1/24.4 were tested aboard RV TINRO in the Bering Sea using the acoustic equipment «Scanmar» (Norway). Possible errors in the estimates of marine organisms abundance by bottom trawl survey are calculated for different species by comparing the actual data on the trawl geometry with the fixed constant value of its horizontal opening. The obtained data can be used for evaluation of the hauled area in bottom trawl surveys.